Evaluation of Human Body Fluids for the Diagnosis of Fungal Infections. (1st August 2013) - Badiee, Parisa
Abstract : Invasive fungal infections are a major cause of morbidity and mortality in immunocompromised patients. Because the etiologic agents of these infections are abundant in nature, their isolation from biopsy material or sterile body fluids is needed to document infection. This review evaluates and discusses different human body fluids used to diagnose fungal infections.